Durasi Kembalinya Kesuburan Paska KB Cyclofem dan Depo Medroksiprogesteron Asetat - Munaf, Ade Zakiya Tasman (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2020)
Cyclofem and Depo Medroxy Progesterone Acetate (DMPA) are the most common types of contraception and are widely used, although there are still drawbacks such as disturbing menstrual patterns, weight gain, and delayed return of fertility. This study aims to determine the difference in the return of fertility between post-Cyclofem and DMPA acceptors in Gorontalo. 40 pregnant women were used in this study with the sampling technique used is purposive sampling. The study was conducted from May 25 to June 8, 2018. The data obtained were then analyzed using the independent t-test. The results showed that the return of fertility after Cyclofem was 7.1 months, and DMPA was 12.9 months. The value of t-count = 3.058 and sig. 0.004. There is a difference in the length of return of fertility between post-Cyclofem and DMPA family planning acceptors in Gorontalo. A larger research sample is needed so that the results obtained are better.